Unravelling the illusion of flicker fusion. (28th February 2017) - Umeton, Diana; Read, Jenny C. A.; Rowe, Candy
Abstract : For over 150 years, researchers have investigated the anti-predator function of animal patterns. However, this work has mainly focused on when prey remain still, and has only recently started to incorporate motion into the study of defensive coloration. As motion breaks camouflage, a new challenge is to understand how prey avoid predators while moving around their environment, and if a moving prey can ever be camouflaged. We propose that there is a solution to this, in that a 'flicker fusion effect' can change the appearance of the prey in the eyes of their predators to reduce the chances of initial detection. This effect occurs when a high contrast pattern blurs at speed, changing the appearance of the prey, which may help them better match their background. Despite being widely discussed in the literature, the flicker fusion effect is poorly described, there is no clear theoretical framework for testing how it might reduce predation, and the terminology describing it is, at best, rather confusing. Our review addresses these three key issues to enable researchers to formulate precise predictions about when the flicker fusion effect occurs, and to test how it can reduce predation.